Development of chemical practice guides class xi project based to improve student’s chemical learning outcomes on acid base materials - Bajoka Nainggolan; Ita Sri Apika Pinem; Wesly Hutabarat (Pascasarjana Universitas Negeri Medan, 2018)
Abstract: This study aims to obtain a standard project-based laboratory chemistry guide for class XI students of Second semester on acid base material. The sample consists of 3 tutorial guide publisher A, B, and C, 2 teacher of senior high school (SMA) 4 Medan, 2 Unimed chemistry lecturer and 2 class XI SMA 4 Medan. Research is descriptive and experimental development with ADDIE models. The results show that the guides have been developed and the standards are in accordance National Education Standards Agency (BSNP). Result validation practice guides developed get the average score of 3.48 times higher than the standard practicum guide A = 3.18, B = 3.32; and C= 30.75. Experimental practice test improves the average learning outcomes of experimental class 1 (using development guide) 70.8% and experiment 2 (using textbook) 54.1%. Psychomotoric and affective grade experiment class 1 higher than the experimental class 2. The resultant learning improvement data was analyzed by right t test. Test of t-test for learning result obtained t count and t table, 6.68 and 1.678, respectively, at level 0.05. This indicates that the project-based practice guide has been well developed and feasible for chemical learning in senior high school.Keywords:acid base material; development; laboratory guide; project based learning